Analisis Penilaian Guru mengenai Peran Manajemen Mutu Pendidikan terhadap Keberhasilan Belajar dan Hambatannya - Robiyah, Ai Iyay; Mardiana, Andi; Nuryani, Lilis Kholisoh (Universitas Cokroaminoto Palopo, 2024)
Learning success is the goal of educational institutions. Teachers as executors in the teaching and learning process have direct experience and assessments of the influence of the quality of education on learning success. The teacher’s perspective on the effect of educational quality in determining learning success and the obstacles that occur during the process are important to know as a basis for institutional management. This study aims to explore the teacher’s subjective assessment of the influence of educational quality on learning success, and the obstacles. The online survey method was used in this study. Six questions consisting of questions with a Likert scale and open-ended qustions were given to participants. As many as 27 participants from an educational institution were involved in this study. Descriptive analysis was carried out in exploring the data obtained. The result showed that teachers generally judge that quality of education influences learning success. Although there ara teachers who judge not so. Obstacles in improving the quality of education in supporting the success of learning exist in the infrastructure and quality of employess. Institutional support and improvement of infrastructure are considered to be a solution to improve the quality of education to support the learning success. Future research can compare the teacher’s subjective assessment with an objective assessment based on standards to obtain an overview of the alignment of the results.